Dominant factors of physical ability determining the achievement of artistic gymnastic techniques - Qomarrullah, R.; Kristiyanto, A.; Sugiharto, M.; Hidayatullah, M. F. (Advances in Social Science, Education and Humanities Research, 2018)
The vault tool in artistic gymnastics is a sport with high-performance parameters, and it belongs to anaerobic. The maximum technique achievement in the vault is strongly supported by elements of good physical performance. The study aims to analyze the relationship of physical ability factor of running speed, the strength of; leg muscle, arm muscle, abdominal muscle, and balance to the achievement of vault technique. The study involved 137 artistic gymnastics athletes aged 10 to 12 years who participated in the junior competition in Central Java Province Indonesia. The study consists of two stages: first, physical ability using 20 m run test, vertical jump, push-up, sit-up, static balance test; second, technical skills are obtained from forwarding handspring movements and round-off entries. Physical and technical capability data were collected twice, and the best score was taken. The data of the research were analyzed using SPSS AMOS 22.0. The results showed that the speed and running factor did not significantly influence; leg muscle strength factor, arm muscle strength, and abdominal muscle strength have a significant effect. The most dominant factor of physical achievement ability of vault technique is leg muscle strength, while the smallest influence is at run speed